Análisis jurídico de la procedencia del pago de pensión alimenticia aun cuando el menor no se encuentre separado del alimentante en el cantón San Miguel en el año 2021. - Vásquez Díaz, Daniela Salome (2023)
The general objective of this investigation is to carry out a doctrinal legal analysis regarding the origin of the payment of alimony even when the minor is not separated from the obligor, since in the Ecuadorian legal system there is no such thing as that, the principal obligor can request a direct provision for the payment of alimony when they are living under the same roof as the fed, which harms their rights, since it implies a double burden, for which a reform is necessary that prioritizes their rights. For the development of the investigation, the inductive method was used, which allowed to study the problem in a particular way and thus reach the general conclusions, the deductive method, which allowed to carry out a logical reasoning and deduce the respective conclusions described in the research document, the method analysis allowed the investigated problem, the techniques that were used for the collection of information was , the survey was carried out on the judges of the Multicompetent Judicial Unit and legal professionals in free exercise of the San Miguel Canton, who in their daily work are in full knowledge of the studied problem. The results of the investigation show that it is necessary to establish a legal reform in which a reform to the Code of Childhood and Adolescence is established where the direct provision to alimony is arranged when the main and fed obligor are under the same roof, in this way the rights of the obligee will not be violated by this legal provision that is legally established in the Code of Childhood and Adolescence. Keywords: Alimony, Rights, Patrimony, Alimony, Legal security.